PERSENTASE SERANGAN HAMA KUMBANG (Oryctes rhinoceros L.) PADA TANAMAN KELAPA(Cocos nucifera L.) DI KECAMATAN TOMBATU KABUPATEN MINAHASA TENGGARA - Erwin Nando Kojong; Vivi B. Montong; James B. Kaligis; Diane D. Pioh (COCOS, 2019)
ABSTRACT Cocos plants ( cocos nucufera L ) are versatile plants, because almost all parts of these plants can be processed and utilized by humans. The production of coconut is very important for human along with the amound off production that always fluctuates from years. Another factor that can inhibiti the growth of coconut is a pest attack. This research aims to determine the percentage of Oryctes rhinoceros L (coconut rhinoceros beetle) attacks on coconut ( Cocos nucifera L.) in Tombatu Subdistrict, Southeast Minahasa District which is housed in five gardens.( polong gardens, Bangataas gardens, Derel gardens, Bendo gardens and Linowit gardens, during three months start from October to December 2019. This research uses survey method or direct observation at the location. The percentage of O. rhinoceros attack in the first to fifth observation each farm was as follows: (1) Bangataas garden 42,52%, (2) Polong garden 32.51%, and (3) Linowit garden 15.46%, (4) Bendo garden 14,32% and (5) Derel garden 13,8%. Keywords: percentage, O rhinoceros, Coconut